Optimizing Civics Learning in High School through the Use of Print Books and Online Learning Resources - Wijaya, Jessica; Asriati, Nuraini (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Pancasila and Citizenship Education (Civics) is one of the core subjects in the Indonesian education curriculum. Along with the development of ICT, Civics learning began to evolve from the use of printed books to the utilization of online learning resources. Both learning resources have their own advantages and are equally needed by students in the context of learning, so from this it is necessary to adjust the Civics teaching method with current technological developments. Therefore, the purpose of this study is to identify and analyze the optimal strategies for utilizing printed books and online learning resources to improve the quality of Civics learning in high schools. This research was qualitative and used the literature study method and data analysis techniques in the form of an interactive model. The results of the study showed that teachers can optimally improve Civics learning in high school by integrating printed books and online learning resources by first understanding in depth the Civics curriculum in high school, then making lesson plans that combine printed books and online learning resources and Learning Management System (LMS), applying project-based learning methods, giving online assignments related to printed book materials, fostering students' digital literacy to find accurate and reliable learning sources, using multimedia such as learning videos from YouTube and implementing simulations. Finally, teachers should evaluate their teaching strategies regularly and collect feedback from students through surveys or class discussions. Integrating printed books and online learning resources can provide students with a more interactive and comprehensive learning experience.